Automated electrical characterization setup for aerosol-jet-printed dielectric elastomer transducers - Martin, Sina; Kaßner, Sebastian; Bruns, Arne; Schärfe, Paul; Reitelshöfer, Sebastian; Franke, Jörg (Online international conference on Electromechanically Active Polymer (EAP) transducers & artificial muscles, 2021)
For the production of stacked and individually shaped dielectric elastomer (DE) transducers, the aerosol-jet-printing had been chosen and further developed at our institute. This printing technology allows the alternating direct deposition of thin layers of either silicone dielectrics or reduced graphene particle electrodes. As the layers are deposited line-wise the surface quality is an issue that has to be considered to obtain constant and predictable electro-mechanical parameters. Typically the characterization of those material systems is performed following the standards for DE testing by Carpi, et al. Based on this established standard we built up our test bench for mechanical and electrical multi-analysis of the printed DE. Furthermore, the setup has been automated to make DE characterization more precise and to facilitate the comparison of a large number of samples in order to create a validation routine to optimize the production process. To allow precise positioning of the specimen the four-axis have been motorized and the program interfaces are used to align the generated information with other measurable parameters such as environmental conditions or timestamps.<br
Keywords: Dielectric elastomer transducers; automated measurement; testing standards; system charcterization